# Characterizing units in polynomial rings

I am trying to prove a result, for which I have got one part, but I am not able to get the converse part.

Theorem. Let $R$ be a commutative ring with $1$. Then $f(X)=a_{0}+a_{1}X+a_{2}X^{2} + \cdots + a_{n}X^{n}$ is a unit in $R[X]$ if and only if $a_{0}$ is a unit in $R$ and $a_{1},a_{2},\dots,a_{n}$ are all nilpotent in $R$.

Proof. Suppose $f(X)=a_{0}+a_{1}X+\cdots +a_{n}X^{n}$ is such that $a_{0}$ is a unit in $R$ and $a_{1},a_{2}, \dots,a_{r}$ are all nilpotent in $R$. Since $R$ is commutative, we get that $a_{1}X,a_{2}X^{2},\cdots,a_{n}X^{n}$ are all nilpotent and hence also their sum is nilpotent. Let $z = \sum a_{i}X^{i}$ then $a_{0}^{-1}z$ is nilpotent and so $1+a_{0}^{-1}z$ is a unit. Thus $f(X)=a_{0}+z=a_{0} \cdot (1+a_{0}^{-1}z)$ is a unit since product of two units in $R[X]$ is a unit.

I have not been able to get the converse part and would like to see the proof for the converse part.

• If $x$ is nilpotent then $1-x$ is a unit. – PrimeNumber Jan 26 '11 at 20:47
• @Chandru1: $\ u$ unit, $z^n = 0\ \Rightarrow\ u-z\ |\ u^n - z^n = u^n,\$ so $\ u - z\$ is a unit, being a divisor of the unit $u^n\:.\$ Thus $\$ unit + nilpotent = unit. – Bill Dubuque Jan 30 '11 at 19:16

## 2 Answers

If $R$ is a domain then easily $f(X)$ a unit implies that $a_i = 0$ for $i>0$. Now $R\to R/\mathfrak p$, for $\mathfrak p$ prime, reduces to the domain case, yielding that the $a_i$, $i>0$ are in every prime ideal. But the intersection of all prime ideals is the nilradical, the set of all nilpotent elements - as you proved a few days ago.

See also my post here on reduction to domains by factoring out prime ideals.

• See here for units in the Laurent polynomial ring $R[x,x^{-1}]\ \$ – Bill Dubuque Jun 28 at 12:43

Let $$f=\sum_{k=0}^n a_kX^k$$ and $$g= \sum_{k=0}^m b_kX^k$$. If $$f g=1$$, then clearly $$a_0,b_0$$ are units and:

$$a_nb_m=0$$ $$a_{n-1}b_m+a_nb_{m-1}=0 \Rightarrow (a_n)^2b_{m-1}=0$$ $$a_{n-2}b_m+a_{n-1}b_{m-1}+a_nb_{m-2}=0 \Rightarrow (a_n)^3b_{m-2}=0$$ $$.....$$ $$.....+a_{n-2}b_2+a_{n-1}b_1+a_nb_0=0 \Rightarrow (a_n)^{m+1}b_{0}=0$$

Since $$b_0$$ is an unit, it follows that $$(a_n)^{m+1}=0$$.

Hence, we proved that $$a_n$$ is nilpotent, but this is enough. Indeed, since $$f$$ is invertible, $$a_nx^n$$ being nilpotent implies that $$f-a_nX^n$$ is unit and we can repeat (or more rigorously, perform induction on $$\deg(f)$$).

• Why does $a_{n-1}b_m+a_nb_{m-1}=0 \Rightarrow (a_n)^2b_{m-1}=0$ ? – Nethesis Oct 3 '14 at 0:45
• Wait, got it, though surely that is only true if $a_n \in (Z)R$? – Nethesis Oct 3 '14 at 0:46
• @Nethesis If by $Z$ you mean the center, it is probably because the ring is given commutative ;) – N. S. Oct 3 '14 at 1:15
• Ah right, sorry, I was looking for an answer about a non commutative ring and din't see that in the question, my bad @N.S. – Nethesis Oct 5 '14 at 17:40
• @zed111 In a commutative ring you have unit-nilpotent=unit. The proof is easy: if u is unit and v is nilpotent, then $v^n=0$ which means $$u^n=u^n-v^n=(u-v)(u^{n-1}+u^{n-2}v+...+v^{n-1})$$ This shows that $$(u-v)(u^{n-1}+u^{n-2}v+...+v^{n-1})(u^{-1})^n=1$$ – N. S. Apr 20 '15 at 15:47

## protected by user26857Nov 21 '15 at 23:01

Thank you for your interest in this question. Because it has attracted low-quality or spam answers that had to be removed, posting an answer now requires 10 reputation on this site (the association bonus does not count).

Would you like to answer one of these unanswered questions instead?